Kara Walker after the deluge - Walker, Kara 1969- (Rizzoli, 2007)
Inspired by Hurricane Katrina and its aftermath, an African-American artist explores the politics of race, slavery, and gender through a series of images from the South, with examples of her work juxtaposed with historical art works.